Kidney disease and electrolytes in COVID-19: more than meets the eye - Carriazo, Sol (Clin Kidney J, 2020)
COVID-19 is a global pandemic fuelled in some countries by government actions. The current issue of Clinical Kidney Journal presents 15 articles on COVID-19 and kidney disease from three continents, providing a global perspective of the impact of severe acute respiratory syndrome coronavirus 2 on electrolytes and different kidney compartments (glomeruli, tubules and vascular compartments) and presenting clinically as a syndrome of inappropriate antidiuretic hormone secretion, acute kidney injury, acute kidney disease, collapsing glomerulopathy and thrombotic microangiopathy, among others, in the context of a brand-new cardiorenal syndrome. Kidney injury may need acute dialysis that may overwhelm haemodialysis (HD) and haemofiltration capabilities. In this regard, acute peritoneal dialysis (PD) may be lifesaving. Additionally, pre-existent chronic kidney disease increases the risk of more severe COVID-19 complications. The impact of COVID-19 on PD and HD patients is also discussed, with emphasis on preventive measures. Finally, current therapeutic approaches and potential future therapeutic approaches undergoing clinical trials, such as complement targeting by eculizumab, are also presented.